Recent advances in organocatalytic atroposelective reactions - Henrich Szabados; Radovan Šebesta (Beilstein Journal of Organic Chemistry)
Axial chirality is present in a variety of naturally occurring compounds, and is becoming increasingly relevant also in medicine. Many axially chiral compounds are important as catalysts in asymmetric catalysis or have chiroptical properties. This review overviews recent progress in the synthesis of axially chiral compounds via asymmetric organocatalysis. Atroposelective organocatalytic reactions are discussed according to the dominant catalyst activation mode. For covalent organocatalysis, the typical enamine and iminium modes are presented, followed by N-heterocyclic carbene-catalyzed reactions. The bulk of the review is devoted to non-covalent activation, where chiral Brønsted acids feature as the most prolific catalytic structure. The last part of the article discusses hydrogen-bond-donating catalysts and other catalyst motifs such as phase-transfer catalysts.